2020
DOI: 10.3390/ijms21041484
|View full text |Cite
|
Sign up to set email alerts
|

CLIC1 Protein Accumulates in Circulating Monocyte Membrane during Neurodegeneration

Abstract: Pathologies that lead to neurodegeneration in the central nervous system (CNS) represent a major contemporary medical challenge. Neurodegenerative processes, like those that occur in Alzheimer’s disease (AD) are progressive, and at the moment, they are unstoppable. Not only is an adequate therapy missing but diagnosis is also extremely complicated. The most reliable method is the measurement of beta amyloid and tau peptides concentration in the cerebrospinal fluid (CSF). However, collecting liquid samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Since soluble and fibrillar Aβ are both able to induce ROS production in microglia it is reasonable to think that this is the cellular subtype where tmCLIC1 inserts forming a functional channel. In a recent study it was shown that peripheral blood mononuclear cells (PBMC) and, in particular, monocytes, isolated from Alzheimer’s Disease patients show an overexpression of CLIC1 mRNA that is accompanied by a significative increase in transmembrane protein [ 50 ]. The authors concluded that the study could pave the way for future developing strategies aimed at discriminating between healthy and patients with ongoing neurodegenerative processes.…”
Section: Clic1 During Chronic Allostasismentioning
confidence: 99%
“…Since soluble and fibrillar Aβ are both able to induce ROS production in microglia it is reasonable to think that this is the cellular subtype where tmCLIC1 inserts forming a functional channel. In a recent study it was shown that peripheral blood mononuclear cells (PBMC) and, in particular, monocytes, isolated from Alzheimer’s Disease patients show an overexpression of CLIC1 mRNA that is accompanied by a significative increase in transmembrane protein [ 50 ]. The authors concluded that the study could pave the way for future developing strategies aimed at discriminating between healthy and patients with ongoing neurodegenerative processes.…”
Section: Clic1 During Chronic Allostasismentioning
confidence: 99%
“…CLIC1 (Chloride Intracellular 1) encodes a chloride ion channel protein involved in many necessary cellular functions including the regulation of cell membrane potential, and the proliferation and differentiation of cells(57), including a role in axonal outgrowth of neurons 51 . In addition to neurons, CLIC1 has been found to be expressed in many different tissue types(59), and in particular, CLIC1 protein has been found to accumulate in peripheral blood mononuclear cells (PBMCs) when the central nervous system is in a state of chronic inflammation(58), and increased CLIC1 expression has been shown to occur in microglia stimulated by the presence of β-amyloid in vitro (60,61). Therefore, CLIC1 may potentially act as a biomarker for neurodegenerative disorders such as Alzheimer’s disease, and downregulation of CLIC1 has been shown to have a neuroprotective effect in the presence of β-amyloid proteins(58,6062).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neurons, CLIC1 has been found to be expressed in many different tissue types(59), and in particular, CLIC1 protein has been found to accumulate in peripheral blood mononuclear cells (PBMCs) when the central nervous system is in a state of chronic inflammation(58), and increased CLIC1 expression has been shown to occur in microglia stimulated by the presence of β-amyloid in vitro (60,61). Therefore, CLIC1 may potentially act as a biomarker for neurodegenerative disorders such as Alzheimer’s disease, and downregulation of CLIC1 has been shown to have a neuroprotective effect in the presence of β-amyloid proteins(58,6062). Variants in CLIC1 may contribute to risk of multiple psychiatric disorders and behaviors, such as schizophrenia, MDD and PTSD, as well as many autoimmune and immune-related phenotypes such as asthma and systemic lupus erythematosus(50–53),(63) ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested it might play a role in DNA damage repair and nucleocytoplasmic RNA transport. CLIC1 has been implicated in other psychiatric disorders, but its primary function is inflammasome regulation 6971 . In addition, 6/10 genes had highly consistent directions of effect.…”
Section: Discussionmentioning
confidence: 99%